PD-L2 regulates B-1 cell antibody production against phosphorylcholine through an IL-5–dependent mechanism - McKay, Jerome T. (J Immunol, 2017)
B-1 cells produce natural antibodies which provide an integral first line of defense against pathogens while also performing important homeostatic housekeeping functions. In this study, we demonstrate programmed cell death 1 ligand 2 (PD-L2) regulates the production of natural antibodies against phosphorylcholine (PC). Naïve PD-L2-deficient (PD-L2(−/−)) mice produced significantly more PC-reactive IgM and IgA. This afforded PD-L2(−/−) mice with selectively enhanced protection against PC-expressing non-typeable Haemophilus influenzae (NTHi), but not PC-negative NTHi, relative to wild type mice. PD-L2(−/−) mice had significantly increased PC-specific CD138(+) splenic plasmablasts bearing a B-1a phenotype, and produced PC-reactive Abs largely of the T15 idiotype. Importantly, PC-reactive B-1 cells expressed PD-L2 and irradiated chimeras demonstrated B cell-intrinsic PD-L2 expression regulated PC-specific Ab production. In addition to increased PC-specific IgM, naïve PD-L2(−/−) mice and irradiated chimeras reconstituted with PD-L2(−/−) B cells had significantly higher levels of IL-5 – a potent stimulator of B-1 cell Ab production. PDL2 mAb blockade of wild type B-1 cells in culture significantly increased CD138 and Blimp1 expression and PC-specific IgM, but did not affect proliferation. PDL2 mAb blockade significantly increased IL-5(+) T cells in culture. Both IL-5 neutralization and STAT5 inhibition blunted the effects of PDL2 mAb blockade on B-1 cells. Thus, B-1 cell-intrinsic PD-L2 expression inhibits IL-5 production by T cells and thereby limits natural Ab production by B-1 cells. These findings have broad implications for the development of therapeutic strategies aimed at altering natural Ab levels critical for protection against infectious disease, autoimmunity, allergy, cancer, and atherosclerosis.